La valoración de los medios de prueba, con criterio de comunidad de pruebas, en las sentencias de delitos de violación sexual de menor de edad en el distrito judicial de la libertad entre los años 2010-2014, consolidan la seguridad jurídica - Bocanegra Haro, Leydi (2016)
In the current times the criminal index goes in increase, between them we have the crime of sexual violation of minor, who has turned into a serious problem for the company, although devastating consequences arise in the victims, between them the sexual indemnity of the minors. It is for it that the present qualified investigation " " The valuation of the means of test, with criterion of community of tests, in the judgments of crimes of sexual violation of minor in the Judicial District of the Freedom between the years 2010-2014, they consolidate the juridical safety " pipe as aim to determine the valuation of the means of test with criterion of community of test, in the judgments of the crimes of sexual violation of minor. The present work corresponds to a descriptive work, although we have taken as a base the doctrine, the jurisprudence, the procedural norm, the Plenary Agreement N ° 1-2011/CS-116 as well as the judgments of study. The sample has been six judgments issued by the different jurisdictional organs of the Top Court of Justice of The Freedom, the same ones that have been analyzed being able to conclude that the judges realize the valuation of the test with criterion of community of tests managing to solve and value the same ones for every case in concretly, consolidating the juridical safety